ANALISIS KEBIJAKAN PENENTUAN KEBUTUHAN PENDIDIKAN DAN PELATIHAN PEGAWAI NEGERI SIPIL DI JAWA TIMUR - i d i, S a m (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
Providing education and training of civil servants is always based on a system which isa series of 3 (three) stages, namely 1) determination of educational and training needs;2) the education and training; and 3) evaluation of post education and training. Theineffectiveness of the implementation of policy determination of the needs of educationand technical training as well as functional is affected by 4 (four) factors: a lack ofeffective communication, inadequate resources, disposition or necessary tendency of theparties concerned still needs to be improved and the bureaucratic structure of Board ofEducation and Training East Java Province who have not specified the task ofidentifying the needs of education and training into staff duties. Based on the results ofthe study as stated, so that the implementation of policy determination of the needs ofeducation and technical training as well as functional can achieve maximum resultscompared with the current, then the determination of need for education and trainingwould need to be addressed more effectively based on needs analysis and anyorganization providing education and technical and functional training should be basedon educational needs and appropriate training. Model analysis of the correspondingneed at the moment is T-NAT that can be tested and adapted to conditions of Board ofEducation and Training of East Java province at this time.Keywords: Policy Analysis, Education and Training of Civil Servants